Environmental covariates of sablefish (Anoplopoma fimbria) and Pacific ocean perch (Sebastes alutus) recruitment in the Gulf of Alaska. (October 2016) - Coffin, Brendan; Mueter, Franz
Abstract: The sablefish ( Anoplopoma fimbria ) and Pacific ocean perch (POP; Sebastes alutus ) fisheries in the Gulf of Alaska (GOA) are both highly lucrative and variable. Determining environmental factors that drive variability in their recruitment may improve our understanding of forces affecting their early life survival, which may be helpful when evaluating management strategies. Here we examine relationships between sablefish and POP recruitment and multiple environmental indices associated with circulation in the GOA. We used hierarchical cluster analysis to determine spatially and seasonally relevant scales for analyzing these relationships. We then used structural equation modeling to examine sequential relationships between large-scale climate variables, regional (eastern and western GOA) environmental variables, and recruitment using both hypothesis-testing and exploratory approaches. Exploratory analyses revealed that sablefish recruitment was positively related to July upwelling-favorable winds and negatively related to late winter freshwater discharge in the eastern GOA during age 1. POP recruitment was negatively related to June upwelling-favorable winds in both regions during ages 0 and 1 and positively related to late spring freshwater discharge throughout the GOA during age 1. These results suggest that upwelling-favorable winds and freshwater discharge may affect recruitment of both species through productivity-related mechanisms, and may additionally affect POP recruitment through advection-related mechanisms. Targeted studies at the appropriate scales are needed to provide greater certainty in the potential mechanisms behind these relationships.